Microbial cell wall distruption by electroporation - Muhammad Faris Hanif, Yusoff (2016)
Electroporation technique was conducted in these project with an objective to disrupt the microbial cell wall. In these experiment, two factor are to be consider to know the best condition for electroporation method. Firstly, the effect of distance between two electrode and the effect of treatment time towards the sample of yeast. The objective can be justified by two method, Colony Forming unit (CFU) and FESEM analysis. In CFU method, two experiment with 4 test was conducted. First experiment was 2 cm electrode distance with the treatment time for test 1 was 4 minutes and test 2 of 10 minutes. The second experiment, 4 cm electrode distance with treatment time for test 1 was 4 minutes and test 2 of 10 minutes. Based on the result, we can conclude that the trend show as the treatment time increase, the CFU count decreases. FESEM analysis show the breakup of the cell wall. Two image of untreated yeast cell and treated yeast cell with electroporation was compared ell. Treated yeast cell show the breakup of the cell wall. The optimum condition of electroporation was then being analyzed. From the result, we can conclude that the optimum condition for electroporation technique were determined to be 2 cm electrode distance and 4 minutes of treatment time due to some factor. As a conclusion, the objective of these experiment is achieved by the breaking of the cell wall and extraction of lipid content.